Integrating Paulownia in Agroforestry Systems - Prospects and Potential in India - Singh, Charan; Dhyani, S. K.; Raizada, A. (Indian Journal of Agroforestry, 2020)
Paulownia - a multipurpose tree species indigenous to China has recently been introduced in India. In its native habitat, Paulownia has a very wide adaptability and distribution. Due to its growth habit, crown architecture and root system it is an ideal agroforestry tree. Various Paulownia-crop intercropping (PCI) models had been developed by the farmers in China. A number of crops are being successfully grown with Paulownia under different agro-climatic regions in China. In India, Paulownia was introduced in the year 1993. Regional trials in different parts of the country indicated its good adaptability and growth potential. Paulownia as a agroforestry tree has also been experimented in various parts of the country with encouraging results. The paper reports its growth performance, adaptability to different biophysical conditions and compares it with another fast growing and popular species’ of the region Populus deltoides. The research results indicated that Paulownia has great potential as a multipurpose tree species suitable for agroforestry systems in different biophysical conditions. It also enumerates the future research needs to establish the species on large scale.